A differentiated Ca2+ signalling phenotype has minimal impact on myocardin expression in an automated differentiation assay using A7r5 cells. (June 2021) - Kim, BaRun; Molina, Renato; Jensen, Gabrielle; Poburko, Damon
Graphical abstract: Highlights: We describe an automated pipeline for correlative Ca 2+ and immunofluorescence imaging. A7r5 show signs of differentiation: electrical coupling, voltage-gated Ca 2+ entry, and myofilament and myocardin expression. Ca 2+ -release from ryanodine receptors contributes to the spontaneous activation of voltage-gated Ca 2+ channels. Electrical coupling and spontaneous, voltage-gated Ca 2+ entry do not drive α-smooth muscle actin or myocardin upregulation. Abstract: Vascular smooth muscle cells are unusual in that differentiated, contractile cells possess the capacity to "de-differentiate" into a synthetic phenotype that is characterized by being replicative, secretory, and migratory. One aspect of this phenotypic modulation is a shift from voltage-gated Ca 2+ signalling in electrically coupled, differentiated cells to increased dependence on store-operated Ca 2+ entry and sarcoplasmic reticulum Ca 2+ release in synthetic cells. Conversely, an increased voltage-gated Ca 2+ entry is seen when proliferating A7r5 smooth muscle cells quiesce. We asked whether this change in Ca 2+ signalling was linked to changes in the expression of the phenotype-regulating transcriptional co-activator myocardin or α-smooth muscle actin, using correlative epifluorescence Ca 2+ imaging and immunocytochemistry. Cells were cultured in growth media (DMEM, 10% serum, 25 mM glucose) or differentiation media (DMEM, 1% serum, 5 mM glucose). Coinciding with growth arrest, A7r5 cells became electrically coupled, and spontaneous Ca 2+ signalling showed increasing dependence on L-type voltage-gated Ca 2+ channels that were blocked with nifedipine (5 μM). These synchronized oscillations were modulated by ryanodine receptors, based on their sensitivity to dantrolene (5 μM). Actively growing cultures had spontaneous Ca 2+ transients that were insensitive to nifedipine and dantrolene but were blocked by inhibition of the sarco-endoplasmic reticulum ATPase with cyclopiazonic acid (10 μM). In cells treated with differentiation media, myocardin and αSMA immunoreactivity increased prior to changes in the Ca 2+ signalling phenotype, while chronic inhibition of voltage-gated Ca 2+ entry modestly increased immunoreactivity of myocardin. Stepwise regression analyses suggested that changes in myocardin expression had a weak relationship with Ca 2+ signalling synchronicity, but not frequency or amplitude. In conclusion, we report a 96-well assay and analytical pipeline to study the link between Ca 2+ signalling and smooth muscle differentiation. This assay showed that changes in the expression of two molecular differentiation markers (myocardin and αSMA) tended to precede changes in the Ca 2+ signalling phenotype.